The Prevalence of Signs of Thyroid Pathology among Students of the Karaganda Medical University According to the Survey - Kasipovich, Bekov Yernur; Kakenovna, Omarbekova Nazgul; Kanatovna, Akhmetova Mensulu; Vladimirovna, Pozdnyakova Yelena; Kabdollovna, Moldabayeva Altyn; Iltaevna, Umirbaeva Assel; Toleutayevna, Alibieva Dinara; Minbaevich, Alyiev Ondassyn; Sarsenbaevna, Batyrbekova Lyazat (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The objectives of the study were to study the signs of thyroid dysfunction in students at the Karaganda Medical University. MATERIALS AND METHODS: The survey was conducted among students of the Karaganda Medical University in the amount of two hundred people. Statistical methods were used for comparison among students of different courses. RESULTS: Among junior students, signs of thyroid dysfunction were more pronounced than among senior students. More than half of the examined students had a diagnosed thyroid pathology, which was more pronounced in students of one and two courses. CONCLUSION: Undergraduates are more likely to exhibit signs of stress-related thyroid dysfunction.